A ROLE OF SUPEROXIDE DISMUTASE IN DEVELOPMENT OF POST-OPERATION ATRIAL FIBRILLATION IN CORONARY HEART DISEASE PATIENTS - O. A. Rubanenko; O. V. Fatenkov; S. M. Khokhlunov; L. V. Limareva (Российский кардиологический журнал)
Aim. To evaluate the level of superoxide dismutase (SOD) in coronary heart disease (CHD) patients underwent coronary bypass  (CBG), and to estimate  its importance in development of post-surgery atrial fibrillation (PSAF).Material and methods. Totally, 96 patients studied,  with CHD, admitted for CBG. Patients were selected to 2 groups: 1 group — non-PSAF (67 patients, 80,6% males, mean age 57,9±7,3  y.o.), 2 group — with first time AF in early period of CBG (29 patients,  86% males, mean age 64,0±8,4 y.o.).Results. During study period PSAF developed  in 30,2% cases, mean on 4,9±3,8 day after surgery.  Comparing  with group  1, level of SOD was higher in group  2 patients (2589,8±1999,3 U/g vs 1572,8±1275,2 U/g, р=0,034). Patients of group 2 were  older  4 years  in average  (64,0±8,4  vs 57,9±7,3  y., р=0,048),  had  longer duration of cardiovascular pathology (86,9±76,1 months vs 44,3±38,4 m., р=0,002). Patients with PSAF had III functional class of angina (72,4% vs 47,8%, р=0,028) and III functional class of congestive  heart failure (38,0% vs 7,5%, р=0,006), they had larger left atrium (43,5±4,1 mm vs 37,9±3,4 mm, р<0,001).After multifactorial analysis, predictive value remained  for the following: left atrium larger than 41 mm — 5,1 (95% CI, 2,1-9,8, р=0,0005), SOD more than 2948 U/g — 4,4 (95% CI, 1,1-8,9, р=0,04).Conclusion. The study  showed  that  CBG operation  is followed by activation of oxidation stress which is followed by the decrease of SOD concentration, probably due to its consumption.  However, among patients with PSAF there is higher activity of this enzyme.